2016
DOI: 10.1111/jfpp.12835
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Optimization of Ultrasound Assisted Extraction Parameters using Response Surface Methodology for Water Soluble Polysaccharide Extraction from Hazelnut Skin

Abstract: The aim of this study is to evaluate optimum process conditions for water soluble polysaccharides (WSP) of plant waste materials such as hazelnut skin by using response surface methodologies (RSM). Polysaccharides from hazelnut skin were extracted by means of probe type sonication system using distilled water as a solvent with several sonication time, temperature and amplitude. Response surface models were applied by both Box–Behnken Design (BBD) and Central‐Composite Design (CCD) for determining optimal condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Thus the model developed was significant and reliable. Studentized test results were in agreement with experimental runs which showed that all the data points were kept within the limits [34].…”
Section: Validation Of the Modelsupporting
confidence: 75%
“…Thus the model developed was significant and reliable. Studentized test results were in agreement with experimental runs which showed that all the data points were kept within the limits [34].…”
Section: Validation Of the Modelsupporting
confidence: 75%
“…RSM is one of the effective statistical models that has been widely used in the food and pharmaceuticals industries (Pinheiro et al, 2008;Yilmaz & Tavman, 2017). Based on the single-factor experiment, the Box-Behnken design was applied to optimize the UCGE.…”
Section: Rsm Experimental Designmentioning
confidence: 99%
“…At present, the commonly used polysaccharide extraction methods include hot water extraction, acid–base extraction, and ultrasonic‐assisted extraction (Dou et al., 2019; Yilmaz & Sebnem, 2017). These methods have their advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%